1990
DOI: 10.1073/pnas.87.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Metastable intermediates in myoglobin at low pH.

Abstract: Resonance Raman and optical absorption spectra of ligand-free (deoxy) myoglobin and CO-bound myoglobin (MbCO) at pH 2.6 have been measured by using continuous-flow/rapid-mixing techniques. The spectra of deoxy myoglobin at low pH within 6 ms of the pH drop demonstrate that the iron-histidine bond has been ruptured but that the heme is still five-coordinate. Comparison with data from model complexes indicates that a weak-field ligand, such as a water molecule, is coordinated at the fifth position. The Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 29 publications
11
53
0
Order By: Relevance
“…These spectral variations are indicative of the conversion of the aqua six-coordinate high-spin heme (6cHS) native form of the protein [denoted as 6cHS(1)] to a five-coordinated high-spin (5cHS) species. In fact, at acid pH the length of the Fe-proximal histidine bond increases [65], and breaks in ferric Mb below pH 4, whereas a water molecule binds to the iron atom [6466]. Accordingly, the corresponding RR spectrum in the high frequency region (Figure 1B) changes from the core size marker bands typical of a 6cHS heme (ν 3 at 1483 cm −1 and ν 2 at 1563 cm −1 ) [67] to that of a 5cHS heme with a water molecule coordinated to the heme iron atom [64].…”
Section: Resultsmentioning
confidence: 99%
“…These spectral variations are indicative of the conversion of the aqua six-coordinate high-spin heme (6cHS) native form of the protein [denoted as 6cHS(1)] to a five-coordinated high-spin (5cHS) species. In fact, at acid pH the length of the Fe-proximal histidine bond increases [65], and breaks in ferric Mb below pH 4, whereas a water molecule binds to the iron atom [6466]. Accordingly, the corresponding RR spectrum in the high frequency region (Figure 1B) changes from the core size marker bands typical of a 6cHS heme (ν 3 at 1483 cm −1 and ν 2 at 1563 cm −1 ) [67] to that of a 5cHS heme with a water molecule coordinated to the heme iron atom [64].…”
Section: Resultsmentioning
confidence: 99%
“…1 and 5). On the other hand, the electronic absorption spectrum of ferrous H77Y CooA showed the Soret band and a single peak in the Q-band region at 424.0 and 558.5 nm, respectively, which resembled the spectrum of deoxymyoglobin (41) and was typical of five-coordinate, high-spin ferrous hemeproteins. Shelver et al (16) have reported that H77Y CooA cannot be stably reduced by dithionite (although the data are not shown), which is inconsistent with our result.…”
Section: Electronic Absorption and Epr Spectra Of Wild-type Cooa-mentioning
confidence: 99%
“…In particular, the conformation sensitive interaction of the imidazole side chain of the distal histidine greatly impacts the frequency [66]. In an aqueous solution of COHbA at pH 6.5 with glycerol added at a 12.5% (vol/vol) level, the frequency of the Fe-CO band is ~405 cm −1 which corresponds to a distal heme pocket conformation in which the imidazole side chain is in the pocket, as observed under most ambient conditions in the pH range from 6 to 8 [67]. When this same solution of COHbA is encapsulated in an RM at an added volume that matches that which is used to create a ω 0 20x sample for a glycerol free aqueous solvent, there appears a strong second peak at 492 cm −1 .…”
Section: Resultsmentioning
confidence: 99%